Sinodalitas dan Diakonia Gereja Katolik dalam Menyatukan Kemajemukan di Indonesia - Raimundus Awur; Armada Ryanto; Antonius Denni Firmanto (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
This study focuses on the involvement of the Church in interpreting pluralism in Indonesia. This article describes the efforts of the Catholic Church in addressing diversity in Indonesia through two different but complementary research approaches: quantitative method using questionnaires and qualitative method involving literature review. The quantitative approach involves data collection through questionnaires distributed to various members of the Catholic Church. The numerical data generated from the questionnaires are then statistically analyzed to identify patterns, preferences, and common views related to the synodality and diakonia of the Church. Meanwhile, the qualitative approach involves in-depth analysis through literature study, encompassing an understanding of the concepts of synodality and diakonia of the Church, as well as a review of literature relevant to the Indonesian context. This article aims to provide a comprehensive insight into the role of the Catholic Church in addressing differences and promoting unity in the multicultural context of Indonesia. Thus, this article is expected to make a valuable contribution to the understanding and discussion of the challenges and potential of the synodality and diakonia of the Church in unifying diversity in Indonesia.